PENGGUNAAN KAEDAH NYANYIAN DALAM MATA PELAJARAN REKA BENTUK DAN TEKNOLOGI - Hamzah, Norhasyimah; Omar, Roziyati; Ariffin, Arihasnida; Rubani, Siti Nur Kamariah; Subramaniam, Tamil Selvan (Online Journal for TVET Practitioners, 2018)
Learning in Technology and Design subjects in schools is increasingly challenging of the competition and bridging the gap in the use of increasingly modern educational technology. The purpose of this study is to show the use of singing methods that can be used to attract and increase the perception towards the memory of Year 4 students in Technology and Design subjects. The sample of this study consists of 92 respondents from different schools in three schools located near the City zone in Mersing district, Johor. The research instrument is using a questionnaire containing 26 items. Pilot study was conducted at Mersing Integrated Religious Primary School with 30 respondents. The mean value of the study result for interest is 4.93 and the value of memory value is 4.66 using the Statistical Package for Social Sciences (Version 22.0). The findings show that the use of singing methods is at a high level. Analysis data includes mean score, percentage and correlation. This shows that the use of the song method is practiced among primary school students as it not only attracts interest but also adds the memory of the students to mastering a topic in Technology and Design subjects.